THE EFFECTIVENESS OF THE FISHERMAN'S SPECIAL HOUSE PROGRAM IN KOLAKA UTARA DISTRICT - Anis Ribcalia Septiana; Ahmad Farouq Mulku Zahari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this research is to find out how the Rumah Khusus Nelayan “RUSUS” (the Fishermen's Special House) is effective for the fishermen community, especially in Pitulua Village, Lasusua District, North Kolaka Regency. This program consumes a large budget, considering that most of the people in Pitulua Village are still classified as underprivileged and do not have their own place to live. RUSUS program has been a program of the Kementrian Pekerjaan Umum dan Perumahan Rakyat “PUPR” (The Ministry of Public Works and Public Housing). Nationally for the construction of special houses during this period, 9,833 units were carried out in 34 provinces in Indonesia (Ministry of Public Works RI Communication Bureau) in 2020. The Ministry of Public Works and Public Housing will allocate ABPN funds to the people of North Kolaka Regency who are work as a fisherman with the help of at least 50 units of fisherman's houses in 2017 all fishermen's houses have been realized and have been inhabited for 2 years. The current phenomenon, apart from the Covid 19 pandemic, is related to RUSUS construction program, which is still having problems, in this case of RUSUS, which should be intended for fishermen who are less affluent, but in reality there are still middle and upper class people like honorary; there are also those who use it as a temporary residence and the community does not work as a fisherman; RUSUS is owned by his parents, but only his son occupies the house and does not work as a fisherman; there are still many local people who are more entitled to get RUSUS; there are still fisherman communities who occupy houses that cannot be declared as property rights but are still in the status of usufructuary rights for 5 (five) years.